Resistência à fratura entre a resina acrílica e a resina composta em coroas provisórias implanto-suportadas unitárias imediatas anteriores: estudo in vitro - Cardoso, Kátia Vieira [UNESP] (2014)
The purpose of this study was to evaluate the fracture resistance of the immediate implant-supported provisional crown prepared with denture tooth and composite resin, after different surface treatments. Sixty-four screw-retained implant-supported provisional crown were divided into 8 groups (n= 8) according to the crown material, acrylic resin(AR) group1 or composite resin(CR) groups 2 to 8 and surface treatment performed: 1- no surface treatment, and 2- no surface treatment, 3- methyl methacrylate(MM), 4- metal primer(MP), 5- bonding system(BS) 6- alumina air abrasion (Al3O2) +MM, 7- Al3O2+MP and 8- Al3O2+BS. Specimens were subjected to 1x104 thermal cycles at two temperatures (5ºC and 55 ºC) and after that was performed the static mechanical test with a crosshead speed of 0.5 mm/ min until the sample fracture. When the maximum load to failure was analyzed the group 1 (control) had the highest values (332 N ± 67 mean and standard deviation). Compared to the control, groups 2, 3, 4, 6 and 7 were statistically different (P <0.05), with lower values of maximum than the control. Moreover the 5 and 8 groups were similar and showed no statistical difference when compared with the control (p> 0.05). From the analysis of the data in accordance with the methodology used, it can be concluded that the treatment with bonding system is a good option for clinical use, increasing the resistance of implant-supported provisional crowns made with acrylic resin and composite resin.